Maximizing employability and entrepreneurial success: a training program for highly skilled seniors transitioning into freelance consulting - Atarodi, Siavash; Ottmann, Jean-Yves; Mbaye, Papa Alioune Meïssa (Frontiers in Education, 2024)
This paper provides insights into the impacts of a self-employment and entrepreneurship education program for high-skilled long-term unemployed workers aged 45-65 in France during the COVID-19 pandemic. The training program involves individual tutoring, synchronous online classes and lead generation workshops with a freelancing project to design and present to a committee. We studied the impact of the training through an adapted version of the CHEERS questionnaire sent to the trainees six months after the training completion. In contrast to the previous literature, we show promising resultsfor this kind of training. Our results show that this training program not only helps people to start a freelancing career but also prepares many of them to find an employee position after a long period of unemployment. We have also been able to identify the main characteristics of the jobs obtained afterwards that matter to high-skilled senior workers and to describe five trainee profiles through a cluster analysis: (1) enthusiastic but not confident, (2) quick return to salaried employment, (3) focused on freelancing, (4) demanding and disappointed elders, (5) struggling with business tasks.